Networked Learning with Digital Texts - Bayne, Siân (Proceedings of the International Conference on Networked Learning, 2006)
This paper sets out to examine the implications of the academic use of digital text among learners in higher education. Working from the perspective that the study and production of texts - in whatever form - is a defining academic activity, it seeks theoretical and evaluative insight into the effects of the shift in learning contexts from printed to online, digital text. It begins by demonstrating how the metaphors of stability and mutability can be applied to the two forms, and moves on to examine the accounts given by students of their experiences of working with digital text. The paper ends by offering some alternative perspectives on these accounts, each of which suggests that the cultural shift from the print paradigm to the digital mode is one which is rendered problematic by many of the discourses we engage in when we describe the tasks of learning, teaching and scholarship.